Border Radio Quacks, Yodelers, Pitchmen, Psychics, and Other Amazing Broadcasters of the American Airwaves, Revised Edition - Fowler, Gene (University of Texas Press, 2021)
Before the Internet brought the world together, there was border radio. These mega-watt "border blaster" stations, set up just across the Mexican border to evade U.S. regulations, beamed programming across the United States and as far away as South America, Japan, and Western Europe. This book traces the eventful history of border radio from its founding in the 1930s by "goat-gland doctor" J. R. Brinkley to the glory days of Wolfman Jack in the 1960s. Along the way, it shows how border broadcasters pioneered direct sales advertising, helped prove the power of electronic media as a political tool, aided in spreading the popularity of country music, rhythm and blues, and rock, and laid the foundations for today's electronic church. The authors have revised the text to include even more first-hand information and a larger selection of photographs
Description based on online resource; title from PDF title page (publisher's Web site, viewed 27. Sep 2021)
Keywords: SOCIAL SCIENCE / Media Studies